Anti-inflammatory effects of natural polysaccharides: molecular mechanisms and nanotherapeutic applications - Yang, Jihao; Xiong, Kai; Li, Tengzhen; Zhang, Morang; Li, Zhangyun; Wen, Zhili; Jiang, Yuchuan (Frontiers in Immunology, 2025)
Chronic excessive inflammation drives the pathogenesis of diseases such as Heart Failure (HF) and arthritis. Natural polysaccharides, with low toxicity and biodegradability, exert anti-inflammatory effects by regulating core inflammatory signaling pathways (e.g., Nuclear Factor-κB (NF-κB), Mitogen-Activated Protein Kinase (MAPK), Toll-Like Receptor (TLR)) and downregulating pro-inflammatory cytokines including Tumor Necrosis Factor-α (TNF-α), IL-1β, and IL-6. But their poor water solubility and easy breakdown by digestive enzymes limit bioavailability. Nanonization solves these problems by enhancing aqueous dispersibility, reducing enzymatic hydrolysis, and improving targeting efficiency (passive via the Enhanced Permeability and Retention (EPR) effect, active via ligand modification). It also strengthens the inhibition of pro-inflammatory pathways, activates the Nuclear Factor Erythroid 2-Related Factor 2 (Nrf2)/Heme Oxygenase-1 (HO-1) antioxidant pathway, and protects the mucosal barrier. This review is divided into four logical sections—fundamental mechanisms of inflammation and polysaccharide regulation, anti-inflammatory activities of natural polysaccharides, nanonization strategies for efficacy enhancement, and clinical translation potential. It eliminates redundancy, integrates overlapping information, and provides a concise framework to promote the clinical application of polysaccharide-based anti-inflammatory therapies.